Effect of the fluorination of DLC film on the corrosion protection of aluminum alloy (AA 5052) - Rangel, R. C. C. [UNESP]; Souza, M. E. P. [UNESP]; Schreiner, W. H.; Freire, C. M. A.; Rangel, E. C. [UNESP]; Cruz, N. C. [UNESP] (Elsevier B.V. Sa, 2010)
It is presented a study conducted on the physical and electrochemical properties of fluorinated a-C:H films deposited onto a commercial aluminum alloy (AA 5052). The coatings were deposited from mixtures of 91% of acetylene and 9% of argon by plasma immersion ion implantation and deposition technique, PIIID. Total gas pressure was 44 Pa and deposition time (t(dep)) was varied from 300 to 1200 s. The depositing plasmas were generated by the application of radiofrequency power (13.56 MHz, 100W) to the upper electrode and high voltage negative pulses (2400 V. 300 Hz) to the sample holder. Fluorine was incorporated in a post-deposition plasma treatment (13.56 MHz, 70W, 13 Pa) generated from sulfur hexafluoride atmosphere. Chemical structure and composition of the films were investigated using infrared reflectance/absorbance spectroscopy and X-ray photoelectron spectroscopy. The corrosion resistance of the layers was determined by electrochemical impedance spectroscopy (EIS) in a 3.5% NaCl solution, at room temperature. Films presented good adhesion to the substrates and are classified as hydrogenated amorphous carbon (a-C:H) with oxygen traces. Fluorine was detected in all the samples after the post-deposition treatment being its proportion independent on the deposition time. Film thickness presented different tendencies with t(dep), revealing the variation of the deposition rate as a function of the deposition time. Such fluorinated a-C:H films improved the corrosion resistance of the aluminum surface. In a general way the corrosion resistance was higher for films prepared with lower deposition times. The variation of sample temperature with t(dep) was found to be decisive for the concentration of defects in the films and, consequently, for the performance of the samples in electrochemical tests. Results are interpreted in terms of the energy delivered to the growing layer by ionic bombardment. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Fluorinated amorphous carbon; Thin films; PIIID corrosion resistance